Risk-Reduction Strategies for Platelet Transfusion in the United States - Eleftherios C. Vamvakas (The Scientific World Journal)
Despite bacterial culture of platelets, transfusion-associated bacteremia/sepsis (TABS) may occur with a frequency of approximately 1/60,000 platelet transfusions, while an emerging transfusion-transmitted infection (TTI) could reproduce the epidemic of transfusion-transmitted human immunodeficiency virus (HIV) in the future. As platelet pathogen-reduction (PR) systems licensed in Europe may eventually become licensed in the U.S., three alternative strategies for reducing the residual risks of TTIs and TABS may become available in the U.S. in the future: (1) transfusion of (already-available) non–pathogen-reduced single-donor (as opposed to pooled whole-blood-derived [PWBD]) platelets, (2) transfusion of pathogen-reduced single-donor platelets, or (3) transfusion of pathogen-reduced PWBD platelets (if trials of this component are conducted in the U.S. in the future). PR of platelets will increase the risk of mild and moderate (albeit perhaps not severe) bleeding complications and it cannot protect from all pathogens. Compared to PWBD platelets, single-donor platelets can reduce, by at least twofold, the risk of all known and emerging TTIs, as well as the risk of TABS, without incurring any risk. The fewer donor exposures secured by the use of single-donor platelets – especially if combined with collection of red blood cells and/or plasma from the same donation for transfusion to the same recipient through the use of multicomponent apheresis – may also reduce the risk of transfusion-related acute lung injury. To choose between pathogen-reduced and non–pathogen-reduced single-donor platelets, the increased risks of bleeding complications as well as other possible adverse events secondary to PR need to be quantified precisely and weighed against the competing risks of TABS and emerging TTIs.